The aPKC-CBP Pathway Regulates Adult Hippocampal Neurogenesis in an Age-Dependent Manner - Gouveia, Ayden; Hsu, Karolynn; Niibori, Yosuke; Seegobin, Matthew; Cancino, Gonzalo I; He, Ling; Wondisford, Fredric E; Bennett, Steffany; Lagace, Diane; Frankland, Paul W; Wang, Jing (Université d'Ottawa | University of Ottawa, 2016)
While epigenetic modifications have emerged as attractive substrates to integrate environmental changes into the determination of cell identity and function, specific signals that directly activate these epigenetic modifications remain unknown. Here, we examine the role of atypical protein kinase C (aPKC)-mediated Ser436 phosphorylation of CBP, a histone acetyltransferase, in adult hippocampal neurogenesis and memory. Using a knockin mouse strain (CbpS436A) in which the aPKC-CBP pathway is deficient, we observe impaired hippocampal neuronal differentiation, maturation, and memory and diminished binding of CBP to CREB in 6-month-old CbpS436A mice, but not at 3 months of age. Importantly, elevation of CREB activity rescues these deficits, and CREB activity is reduced whereas aPKC activity is increased in the murine hippocampus as they age from 3 to 6 months regardless of genotype. Thus, the aPKC-CBP pathway is a homeostatic compensatory mechanism that modulates hippocampal neurogenesis and memory in an age-dependent manner in response to reduced CREB activity.
Keywords: Age Factors; Animals; Biomarkers; CREB-Binding Protein; Cell Differentiation; Hippocampus; Memory; Mice; Mice, Transgenic; Neurons; Phosphorylation; Protein Binding; Protein Kinase C; Neurogenesis; Signal Transduction